The Role of Work Environment, Workplace Ownership, and Job Insecurity on Barista Work Engagement in Ciamis Regency - Ramadhani, Indi; Bintari, Vivi Indah; Wahid, Nisa Noor; Desiana, Desiana (The Eastasouth Management and Business, 2025)
Along with the proliferation of coffee shops and coffee businesses, the barista profession is increasingly necessary and trending. Job opportunities to become a barista in coffee shops are currently very promising. The need for baristas in the country is very large, especially for baristas who have qualified skills. Therefore, barista work engagement is very important to be considered by coffee shop owners to maintain business survival and so that the coffee shop trend, especially in Ciamis Regency, does not become a short trend and can have an impact on economic growth in Ciamis Regency. The purpose of this study was to determine and analyze the factors that influence barista work engagement in Ciamis Regency. The research method used is a survey method, with data collection techniques using a questionnaire that will be given to local coffee shop baristas in Ciamis Regency as respondents totaling 63. Data analysis in this study used Path Analysis. The results of this study found that the work environment, workplace belonging, and job insecurity affect the work engagement of baristas in Ciamis Regency.